Synthesis and characterization of lignosulfonate/amino-functionalized SBA-15 nanocomposites for the adsorption of methylene blue from wastewater. (23rd January 2020) - Abboud, Mohamed; Sahlabji, Taher; Haija, Mohammad Abu; El-Zahhar, Adel A.; Bondock, Samir; Ismail, Issam; Keshk, Sherif M. A. S.
Abstract : The synthesis, characterization, and methylene blue (MB) adsorption study of a new lignosulfonate/amino-functionalized SBA-15 nanocomposite are described. Abstract : The synthesis, characterization, and methylene blue (MB) adsorption study of a new lignosulfonate/amino-functionalized SBA-15 nanocomposite are described. (3-Aminopropyl)triethoxysilane (APTES) was grafted into SBA-15 to prepare amino-functionalized SBA-15 (N-SBA-15) which was used, along with calcium lignosulfonate (LS), to prepare a new nanocomposite LS/N-SBA-15. The prepared materials were characterized by SEM, TEM, FT-IR, Brunauer–Emmett–Teller, powder XRD, TGA analysis, and Raman spectroscopy. The experimental results indicated that the obtained nanocomposite possesses a high surface area (598 m 2 g −1 ) and a large pore volume (1.059 cm 3 g −1 ). This particular combination of LS and N-SBA-15 endowed this material with good dispersibility and stability in water, and better wettability. The uptake of MB from aqueous solution using the LS/N-SBA-15 nanocomposite was investigated. The adsorption investigation was performed under parameters such as pH, contact time, adsorbent dosage, temperature and initial dye concentration. The results indicated that the addition of LS to N-SBA-15 enhanced the stability of the composite in water, and improved its adsorption capacity of MB, and showed the optimum conditions at 0.05 g dose and pH = 9 during a short contact time less than 10 min. LS/N-SBA-15 exhibited a high adsorption capacity compared to other adsorbents used in the literature for the removal of MB from water. The reusability of this new nanocomposite was also investigated and the results reported. This new nanocomposite can be efficiently employed for the removal of organic dyes from wastewater.